Acute Pancreatitis Caused By Mushroom Poisoning: A Report of Two Cases. (21st January 2016) - Karahan, Samet; Erden, Abdulsamet; Cetinkaya, Ali; Avci, Deniz; Ortakoyluoglu, Adile Irfan; Karagoz, Hatice; Bulut, Kadir; Basak, Mustafa
Of the more than 5000 species of mushrooms known, 100 types are toxic and approximately 10% of these toxic types can cause fatal toxicity. A type of mushroom called Amanita phalloides is responsible for 95% of toxic mushroom poisonings. In this article, we report 2 cases of mushroom poisonings caused by Lactarius volemus, known as Tirmit by the local people. The patient and his wife were admitted to the emergency room with abdominal pain, nausea, and vomiting 20 hours after consuming Lactarius volemus, an edible type of mushroom. The patients reported that they had been collecting this mushroom from the mountains and eating them for several years but had never developed any clinicopathology to date. Further examination of the patients revealed a very rare case of acute pancreatitis due to mushroom intoxication. The male patient was admitted to the intensive care unit while his wife was followed in the internal medicine service, because of her relative mild clinical symptoms. Both patients recovered without sequelae and were discharged. In this article, we aimed to emphasize that gastrointestinal symptoms are often observed in mushroom intoxications and can be confused with acute pancreatitis, thus leading to misdiagnosis of patients. Early diagnosis and appropriate treatment can improve patients' prognosis and prevent the development of complications.